Assessing burnout among health care professionals in a tertiary hospital in Kohalpur, Nepal: a cross-sectional study - Priyadarshini Shah Singh; Gaurav Jung Shah (Journal of Karnali Academy of Health Sciences)
Background: Burnout is a commonly observed psychological phenomenon that occurs due to prolonged stressors at work, which poses a risk to the health of the working population, despite this, it has been neglected due to the growing work pace and work demands imposed on the workers. Low patient care and safety are due to burnout in healthcare professionals, which could hamper their personal lives, as well as, quality of care.